Speaking of “Disorderly” Objects: A poetics of pedagogical discourse. - Graham, LindaJ. (Discourse: Studies in the Cultural Politics of Education, 2007)
To interrogate pedagogical discourses relating to child behaviour as “practices that systematically form the objects of which they speak” this paper features the analysis of three texts through the development and deployment of what might be called a poetics of pedagogical discourse. The principal text is a statement describing “problematic” behaviour in school. Of concern is how this particular statement functions—what does it do and with what effects? Here my analysis will be informed by the examination of two other texts. Each demonstrates techniques in the production of meaning; specifically, how performative language and intertextuality contribute to and enhance the constitutive properties of discourse. The aim is, first, to “try to grasp subjection in its material instance as a constitution of subjects” through the interrogation of discursive practices that, in objectifying and subjugating individual school children, create the condition of possibility for the recognition and classification of disorderly behaviour and behaviour disorders, such as attention deficit hyperactivity disorder. A second, but no less important, aim is to call attention to the dangers inherent to the ways in which child behaviour comes to be described in schools.